2018
DOI: 10.5530/ijper.52.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: The Molecular Mechanisms of Action in Inflammation and Cell Death during Kainate-Induced Epileptogenesis

Abstract: Background: Recent preclinical studies demonstrated the potential antiepileptogenic effect of curcumin. Its molecular pathways in modulating epileptogenesis remain unclear. Objectives: This study investigated the epileptogenic processes induced by kainic acid (KA) and to investigate the antiepileptogenic pathways associated with curcumin therapy. Methods: A single dose of KA 10 mg/kg was used to induce a convulsive status epilepticus in female Wistar rats. After one week of curcumin treatment, gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Even so, the exact mechanisms through which the anti-inflammatory properties of C. longa are implemented are still unknown, although some authors have reported that it upregulates genes related to the anti-inflammatory cytokines and reduces the expression of pro-inflammatory cytokines, such as IL-1β and TNF-α ( Hashemian et al, 2017 ; Yin et al, 2018 ). One other potential mechanism, described by Peng et al (2021) , is the inhibition of the expression of the iNOS gene by C. longa that interferes with the nitric oxide synthase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, the exact mechanisms through which the anti-inflammatory properties of C. longa are implemented are still unknown, although some authors have reported that it upregulates genes related to the anti-inflammatory cytokines and reduces the expression of pro-inflammatory cytokines, such as IL-1β and TNF-α ( Hashemian et al, 2017 ; Yin et al, 2018 ). One other potential mechanism, described by Peng et al (2021) , is the inhibition of the expression of the iNOS gene by C. longa that interferes with the nitric oxide synthase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This compound has shown antiseizure activity in chemical and electrical seizure models in animals [ 10 ] . In addition to antioxidant and anti-inflammatory effects [ 20 - 22 ] , curcumin has demonstrated antiepileptic activities in kainate model of temporal lobe epilepsy [ 12 ] and PTZ kindling model [ 11 ] . These properties might underlie the antiepileptic effect of curcumin, which is observed in our study in TBI state.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is the main ingredient of turmeric with a wide range of pharmacologic activities such as antiseizure, anti-inflammatory, antioxidant, anti-amyloid, anticancer, and neuroprotective effects [ 1 , 9 , 10 ] . The antiepileptic effect of curcumin and the underlying mechanisms are not completely disclosed [ 1 , 11 , 12 ] . Therefore, we aimed to investigate the effect of curcumin pretreatment on epileptogenesis after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The harmful effects, which are toxic to tissues, occur primarily through the production of free radicals [12,13]. This reaction is important in removing damaged cells from the brain tissue; however, it can also increase the harm to brain cells by producing free radicals that are toxic to healthy cells [2,14,15]. There has been an increasing amount of evidence suggesting that ischemic inflammation may be vital to the issue of pathogens, as ischemic stroke results not only in damage and neuronal loss but also in sustained neuroinflammation after stroke [3,16,17].…”
Section: Introductionmentioning
confidence: 99%